Peranan KUD Sembada Puspo sebagai Penggerak Pembangunan Ekonomi Desa Ditinjau dari Perspektif Ekonomi Islam di Kecamatan Puspo Kabupaten Pasuruan - Lailatul Azizah (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2023)
This research is a qualitative descriptive research . Researchers will describe the existence of cooperatives in carrying out the role of developing village economic development. From the results of the analysis, it was found that’’ the role of the Puspo Sembada KUD as the driving force for village development was considered to have a high multiplier effect’’.As a supporter of gross regional domestic product has low competitif power, this is evident from the increase in cow’s milk production that is not accompanied by quality, therefore we need a strategy that focuses on the mechanism and optimization of the development of cow’s milk farmers and target markets, including: provide guidance and counseling to dairy farmers.